FOOD AND FEEDING HABITS OF JUVENILES OF ’KOTH’ OTOLITHOIDES BRUNNEUS (DAY) IN BOMBAY WATERS - Jayaprakash, A A (Indian Journal of Fisheries, 2011)
The food and feeding habits of juveniles of ’Koth’ Otolithoides brunneus (Day), a sciaenid occurring along the coast of Bombay, were studied during the period January 1970 â€” December 1971. O. brunneus a macrophagous carnivore, fed on smaU teleoits and prawns. Index values for main food items during 1970 and 1971 were as ibllows: Prawn remains: 46.15, 40.33; Coilia dussumieri: 16.83, 28.43; Acetes indicus: 7.32, 15.47; Bregmaceros macclellandi: 18.06, 1.42; Palaemon tenuipes: 3.2’[), 5.22; and Hippolysmata ensirostris: 5.29, 0.32 respectively. Besides, teleosts like Otolithes argenteus, Polynemus heptadactylus, Harpodon nehereus, Johnius npp. and Apogon spp., and prawns, such as, Solenocera indica, Metapenaeus affinis M. brevicornis, Parapenaeopsis stylifera and P. hardwickii were ako noticed. The younger juveniles of the size group 7.0 â€” 13.9 cm preferred only prawns. Witli age O. brunneus showed a piscivorous tendency. The food index value of prawns as a whole decreased from the smallest to the larger size groups of ’Koth’. Feeding depended on the availability and no selective feeding was observed. Intense feeding in April, May and November, normal feeding during December, January and March and for the rest of the period low feeding seemed to prevail. The probable causes contributing to the intense feeding have been discussed